2018
DOI: 10.1007/s12031-018-1045-y
|View full text |Cite
|
Sign up to set email alerts
|

Updated Meta-Analysis of BIN1, CR1, MS4A6A, CLU, and ABCA7 Variants in Alzheimer’s Disease

Abstract: Genome-wide association studies (GWAS) have associated several genetic variants with late-onset Alzheimer's disease (LOAD), a neurodegenerative disease. Among those, rs3764650 ABCA7, rs6656401 CR1, and rs744373 BIN1 were associated as risk factors for LOAD, while rs11136000 CLU and rs610932 MS4A6A were protective. Recently, several case-control studies have investigated the association of these polymorphisms with AD. However, not all meta-analyses analyzed these variants across different ethnic groups. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The different SNPs on the BIN1 gene may be in disequilibrium and may add independently from each other to the risk of AD 14 . Here, we focused on rs744373 because this SNP is most frequently reported to be associated with AD across different GWAS studies 3,7 (see also AlzGene database at http://www.alzgene.org/) 50 . Although rs744373 is the primary BIN1 SNP associated with increased AD risk, a previous study suggested that the Indel rs59335482 is associated with increased BIN1 mRNA in post-mortem analyzed brains from AD patients, suggesting that rs59335482 is the functionally effective BIN1 genetic variant associated with AD risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different SNPs on the BIN1 gene may be in disequilibrium and may add independently from each other to the risk of AD 14 . Here, we focused on rs744373 because this SNP is most frequently reported to be associated with AD across different GWAS studies 3,7 (see also AlzGene database at http://www.alzgene.org/) 50 . Although rs744373 is the primary BIN1 SNP associated with increased AD risk, a previous study suggested that the Indel rs59335482 is associated with increased BIN1 mRNA in post-mortem analyzed brains from AD patients, suggesting that rs59335482 is the functionally effective BIN1 genetic variant associated with AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…While late onset AD is an age-related disease, results from twin and family studies have emphasized that ~50% of phenotypic variance in AD can be explained by genetic variations 2 . Recent genome-wide association studies (GWAS) have identified several loci that are associated with increased risk of AD, among which the single nucleotide polymorphisms (SNPs) in the bridging integrator 1 ( BIN1 ) gene show the second highest odds-ratios for sporadic AD, superseded only by apolipoprotein E ( APOE ) variants 37 . Specifically, the most frequently reported BIN1 AD risk variant is the SNP rs744373 which shows a global allele frequency of 37% and is associated with an increase in AD risk by an odds-ratio of 1.17–1.19 5,7–10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other meta-analyses have then confirmed the genetic involvement of ABCA7 with the disease (Almeida, dos Santos, Trancozo, & de Paula, 2018;Ma et al, 2018). To date, the risky G allele of the rs3764650 has been associated with reduced ABCA7 expression, hippocampal atrophy, increased plaque pathology and subsequent cognitive decline (Andrews, Das, Cherbuin, Anstey, & Easteal, 2016;Ma et al, 2018;Ramirez et al, 2016;Shulman et al, 2013;Vasquez, Fardo, & Estus, 2013), whereas the G1527A mutation affected Aβ deposition (Hughes et al, 2014).…”
Section: Abca1 and Abca7mentioning
confidence: 91%
“…However, in spite of the progress in understanding risk factors related to AD development, the underlying mechanisms involved in this disease have not been completely understood till now, and to date there is no curative treatment for AD [5,6]. Now many genes are proved to significantly influence AD risk, among which the complement component (3b/4b) receptor 1 gene (CR1) has been proved to affect AD susceptibility across different ethnic and districts groups [7][8][9][10][11][12]. Currently, CR1 has been postulated to be a key factor for AD pathogenesis because of its role in regulating complement activity by acting as a receptor of complement C3b protein [13].…”
Section: Introductionmentioning
confidence: 99%